Peran Orang Tua dalam Pendidikan Agama Islam Terhadap Anak Berkebutuhan Khusus - Difa’ul Husna; Lia Ni’matul Maula; Nur Fitri Wulandari (Al-Ishlah: Jurnal Pendidikan Islam, 2021)
The role of parents in children's education is very influential on the emotional development of children, the character and attitudes of children, especially children with special needs who in their daily lives still need the role of other people to carry out their activities. Even so, it does not mean that children with special needs become children who are dependent on other people, but if in their daily lives they are educated patiently, repeatedly at least the child can become independent and can get used to their activities. The role of parents in children with special needs can be classified as parents who have roles as motivators, mentors, supervisors, good examples and provide facilities for children's needs and religious facilities. In this study using qualitative research methods by conducting interviews as data collection. After analyzing the data, the researcher can conclude that the role of parents in Islamic religious education has an important role for children by allowing children to go to school, escorting children and accompanying children patiently according to the different ability conditions experienced by children with special needs. Keywords: The Role Of Parents, Islamic Education, The Child With Special Needed.